CITATION ANALYSIS OF POST-GRADUATE THESE OF DEPARTMENT OF AGRONOMY ACCEPTED BY COLLEGE OF AGRICULTURE, CENTRAL AGRICULTURE UNIVERSITY, MANIPUR (2010-2017) - Singh, Laithangbam Nepolean; Phuritsabam, Bobby (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Citation analysis is an effective tool to identify the core references in a subject by counting the citations appended at the end of each scientific article. It is basically a technique, which involves the process of collection, counting, analysis and interpretation of citations given in research writing and thereby helping in identification of significant sources of information. The study is based on the 32 post graduate theses accepted by Dept. of Agronomy, college of Agriculture, Central Agriculture University, Manipur 2010-2017. 3037 citations were found appended in the present study. The study revealed that journals were the most preferred sources of information used by the researchers in the field of Agronomy for 73.96 % of total citations, followed by proceeding with 9.15 % citations. The Indian Journal of Agronomy has ranked the first with 101 citations accounting for 4.49% of the total journal citations. Authorship pattern for journal citations shows that most of the citations were contributed by three authors. (28.71%) The findings of the study also revealed that out of the total number of 2246 journal citation, 44.30% are from India. The highest year were 2001-210; its citation was 697 i.e.31.3%.